Design and development of a website-based information system for receiving diplomas in the information management department of the Fakfak State Polytechnic - Roy, Andi; Maulida Al hamid, Deisya; Ladese, Sudirman; Hasta, Hasta (Jurnal Mandiri IT, 2024)
The need for fast and accurate information is really needed by universities, because fast information will influence policies or steps taken. This requires universities to take concrete steps in providing information. Fakfak State Polytechnic, especially the Informatics Management Department, in the process of collecting, managing and providing information on the requirements for receiving or taking a diploma is still manual. Using technology is one of the right solutions for the rapid dissemination of information. Design of a web-based development diploma recipient information system at the Department of Information Management, Fakfak State Polytechnic. This system emerged as a solution aimed at assisting informatics management students in obtaining their diplomas. The method used by the author in creating this system is the waterfall method starting from the process of planning, analysis, design, writing program code, program testing and program design and system maintenance. The results of this research produced a website that is used to provide information and accommodate files which are a prerequisite for obtaining a diploma.